IMPLEMENTASI KURIKULUM MERDEKA BERBASIS CINTA DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI MADRASAH ULUMUL QUR’AN LANGSA TAHUN AJARAN 2025/2026 - Syafrida; Muhammad Akbar; Gina Anggelina; Zaifaturridha Zaifaturridha; Nazib Baihaqi; Tri Wulandari Dalimunthe (LPPM STAI Ihyaul Ulum Gresik, 2026)
This study aims to analyze the implementation of the love-based Independent Curriculum in the formation of students' character at Madrasah Ulumul Qur'an Langsa for the 2025/2026 Academic Year. This study uses a qualitative approach with a case study method. Data collection techniques are carried out through participatory observation, in-depth interviews with teachers and students, and documentation of learning activities. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing using triangulation techniques to ensure data validity. The results of the study show that the implementation of the love-based Independent Curriculum is carried out through the example of teachers, habituation of the value of compassion, collaborative activities, and the integration of spiritual values in the learning process. The application of this approach is able to create a more humane and conducive learning atmosphere and encourage the development of students' character, such as increased empathy, responsibility, discipline, and social concern. In addition, the interpersonal relationship between teachers and students becomes more positive so as to support the active involvement of students in learning. Thus, the implementation of the love-based Independent Curriculum plays an important role in shaping the character of students who have noble character, independence, and social concern in the madrasah environment.